Veracity as Basic Category of journalistic Discourse: Methodology of Interpretation - Beloedova, Anna (2018)
The category of veracity, as well as objectivity, is declared to be the main principle in the theory and practice of journalism. The journalistic descriptions of categories have their own specificity as compared to philosophical considerations. The veracity of journalistic texts including the closely related categories of objectivity and accuracy are of great importance in contemporary research discourses. The object of the research is scientific concepts of veracity, objectivity, accuracy, facts, knowledge; we focus on their peculiarities and purpose in journalistic discourse. The article deals with approaches and ways of veracity interpretation in mass media. The specific features and purposes of veracity are analyzed. Attention is drawn to multi-dimensionality of the category which is revealed in journalistic texts in connection with informativity, accuracy, objectivity; indicators and criteria of veracity and accuracy in contemporary media texts. Researching of objectivity through sub-categories of informative value, accuracy and objectivity leads to the conclusion that it is more appropriate to take into consideration the interference between objectivity and subjectivity, accuracy and approximation, various types of information required for veracity evaluation.